THE QUESTION OF INTELLECTUAL INGREDIENT OF REFORMATIVE ACTIVITIES OF POLITICAL ELITES - Полисаєв, О. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article analyzes the process of structural reforms in contemporary communities, the main condition of which is theoretical reflection of reformative activities and the realization of scientific results in the real social practice.